2021
DOI: 10.3892/etm.2021.10735
|View full text |Cite
|
Sign up to set email alerts
|

Effects of isoflavone derivatives on the production of inflammatory cytokines by synovial cells

Abstract: The present study investigated the effects of isoflavone derivatives (daidzein, genistein and glycitein) on the production of inflammatory cytokines (IL-6 and IL-8) by IL-1β-stimulated synovial cells. Synovial MH7A cells were stimulated with IL-1β in the absence or presence of isoflavone derivatives, and IL-6 and IL-8 production was measured by ELISA. The results of the present study indicated that daidzein significantly inhibited the production of IL-6, but not IL-8. Conversely, neither genistein nor glycitei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…59 Further study showed that the isoflavone derivative daidzein inhibited IL-6 expression in synovial cells. 60 We now report the apparent regulation of CLL2 and CXC chemokines by soy protein in astrocytes. The reduced production of chemokines by astrocytes may improve the regeneration of wounded neural tissue by grafting of the SPI− collagen hybrid scaffold.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…59 Further study showed that the isoflavone derivative daidzein inhibited IL-6 expression in synovial cells. 60 We now report the apparent regulation of CLL2 and CXC chemokines by soy protein in astrocytes. The reduced production of chemokines by astrocytes may improve the regeneration of wounded neural tissue by grafting of the SPI− collagen hybrid scaffold.…”
Section: Discussionmentioning
confidence: 80%
“…The secretion of chemokines IL-1β, IL-6, and IL-8 by MH7A cells was reduced by the treatment of the soy isoflavone derivative genistein . Further study showed that the isoflavone derivative daidzein inhibited IL-6 expression in synovial cells . We now report the apparent regulation of CLL2 and CXC chemokines by soy protein in astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblast-like synoviocytes synthesizes and secretes mediators of inflammation including IL-6 and IL-8 ( Georganas et al, 2000 ). Furthermore, a large body of literature has proposed that IL-6 and IL-8, two pro-inflammatory factors were generally chosen as pro-inflammatory cytokines ( Li et al, 2014 ; Mijiti et al, 2021 ). Therefore, in this study, IL-1β-induced MH7A cells were selected to construct an in vitro inflammation model to examine the effects of the polyphenols on the pro-inflammatory factors IL-6 and IL-8.…”
Section: Discussionmentioning
confidence: 99%